Preparation of bio-functional textiles by surface functionalization of cellulose fabrics with caffeine loaded nanoparticles. (December 2018) - Massella, D.; Ancona, A.; Garino, N.; Cauda, V.; Guan, J.; Salaun, F.; Barresi, A. A.; Ferri, A.
Abstract: In recent years transdermal drug delivery has aroused significant interest as a sustained and non-invasive way of administering active substances. The advancements of nanotechnology allowed the development of novel pharmaceutical formulations overcoming skin barrier. Furthermore, such nano-system can be combined with conventional fabrics to pave the way to a new generation of wearable drug delivery devices: bio-functional garments. First the NP were produced by flash nanoprecipitation technique (FNP), the production process was optimized to produce particles with suitable size for transdermal applications. The nanoparticles were characterized in terms of drug content by UV-visible spectroscopy and in term of antioxidant activity by Electron Paramagnetic Resonance spectroscopy (EPR) coupled with spin trapping technique. The NPs were used to functionalize cotton and viscose-micromodal fabrics and the transdermal release properties were tested in vitro by Franz's Cell experiment. FNP was proven to be an effective technique to produce tunable size particles. Moreover, the nanoencapsulated drug exhibited antioxidant activity. The Franz's Cell test evidenced a controlled release behavior, providing evidence that the bio-functional textile is suitable for applications where sustained release and antioxidant properties are required.